2020
DOI: 10.1002/agg2.20061
|View full text |Cite
|
Sign up to set email alerts
|

Manganese adsorption, availability, and uptake in citrus under microsprinkler irrigation

Abstract: Manganese deficiencies have been observed in shallow soils with high water tables and in well‐drained sandy soils of Florida. This study investigated Mn leaf uptake in citrus trees on a Florida sandy soil through modified Mn fertilization methods and rates. Tree rows were supplied with three N rates and Mn at single and double the recommended rates (recommended rate: 10.08 kg ha−1) using foliar and soil application methods. The double foliar application rate increased leaf Mn by 20% over the single application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…The current study indicated that no significant increase in TCV was detected as trees receive beyond the 224 N kg ha −1 coupled with foliar (1×) coupled with ground (1×) treatments. Similar results were observed, in which TCV increment was reported when trees received the suggested N rate of 224 kg N ha −1 and foliar Zn nutrition as compared with other N rates and application methods [ 31 ].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The current study indicated that no significant increase in TCV was detected as trees receive beyond the 224 N kg ha −1 coupled with foliar (1×) coupled with ground (1×) treatments. Similar results were observed, in which TCV increment was reported when trees received the suggested N rate of 224 kg N ha −1 and foliar Zn nutrition as compared with other N rates and application methods [ 31 ].…”
Section: Resultssupporting
confidence: 83%
“…Therefore, multiple annual fertilizer applications in association with scheduling fertigation, and products with incorporated elemental sulfur (S) that releases S to lower soil pH were utilized to enhance nutrient availability and minimize the nutrient leaching probability [ 28 , 30 ]. Manganese (Mn) deficiency is normally a worldwide problem predominantly manifested in the spring after a cold winter [ 2 , 31 ]. Severe Zn or Fe deficiencies bring about a delay in recognizing the symptoms of Mn deficiency and subsequent corrective measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle density was determined using the pycnometer method ( Table 1 , [ 12 ]). The soil pH is approximately 6 and organic matter content is less than 0.5% [ 13 , 14 ]. Lowering the pH specifically for this micronutrient’s availability would impair the availability of essentially important macronutrients.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Nutrition plays an important role in plant defense mechanisms against multiple pests and diseases, as well-fertilized plants are less susceptible than nutrient-deficient ones (Garc ıa-Mina, 2012;Spann and Schumann, 2010). Recent evidence suggests that HLB symptoms in citrus can be reduced with a balanced nutritional program, including improved irrigation, fertigation, and nutrient management (Atta, 2019;Atta et al, 2020;Handique et al, 2012;Kadyampakeni et al, 2016;Morgan et al, 2016;Phuyal et al, 2020aPhuyal et al, , 2020bRouse et al, 2012;Uthman et al, 2020bUthman et al, , 2020aZambon et al, 2019). Thus, until commercially available resistant citrus varieties are developed, limiting the effects of HLB by focusing on nutrient management can help keep commercial growers in production (Alvarez et al, 2016;Spann and Schumann, 2010).…”
mentioning
confidence: 99%